Density functional study of half-metallicity and spin polarization in Fe1−xTxS2 with T = Mn, Ni. (2nd July 2018) - Houari, Abdesalem; Blöchl, Peter E
Abstract: Alloying effects by Mn and Ni substitution on FeS2 have been studied using density-functional calculations. Standard generalized gradient approximation (GGA) and local hybrid functional have been utilized to account for exchange-correlations. The alloys Fe1− x T x S2 with T  =  Mn, Ni have been investigated for concentrations together with the ground states of the pure compounds. The electronic structure is discussed with the main goal to identify candidates for ferromagnetic half-metals, which are of interest for spintronics applications. Depending on the used calculation framework, interesting candidates have been found at different concentrations. However, at mean concentration of the Mn-doping and low concentration for Ni-doping, both GGA and hybrid functional agree to predict half-metallic character. For the Mn alloys we also note the proximity to a low-spin to high spin transition.